2019
DOI: 10.1111/ejn.14348
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and cannabinoid receptors modulate impulsive behavior in an animal model of attentional deficit and hyperactivity disorder

Abstract: Attention deficit and hyperactivity disorder (ADHD) is characterized by impaired levels of hyperactivity, impulsivity, and inattention. Adenosine and endocannabinoid systems tightly interact in the modulation of dopamine signaling, involved in the neurobiology of ADHD. In this study, we evaluated the modulating effects of the cannabinoid and adenosine systems in a tolerance to delay of reward task using the most widely used animal model of ADHD. Spontaneous Hypertensive Rats (SHR) and Wistar–Kyoto rats were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 68 publications
(96 reference statements)
1
16
0
Order By: Relevance
“…These results may reflect that the administration of these SCBs triggered impulsive behavior, which has been commonly observed in SCB users (Ozten et al, 2015;Altıntaş et al, 2019). Additionally, these impulsive effects of SCBs are supported by previous studies that cannabinoid receptors are responsible for impulsive behavior (Leffa et al, 2019;Wiskerke et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…These results may reflect that the administration of these SCBs triggered impulsive behavior, which has been commonly observed in SCB users (Ozten et al, 2015;Altıntaş et al, 2019). Additionally, these impulsive effects of SCBs are supported by previous studies that cannabinoid receptors are responsible for impulsive behavior (Leffa et al, 2019;Wiskerke et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…As regard to impulsivity, although an acute pretreatment with caffeine increased choices of large reward on SHR, a chronic treatment with caffeine increased the impulsive phenotype and decreased choices of large reward on SHR [25]. This discrepancy may be explained by previous studies performed on animal models of brain diseases, showing that while an acute treatment acts mainly on A1 receptors, a chronic treatment acts mainly on A2A receptors [32].…”
Section: Discussionmentioning
confidence: 98%
“…Leffa et al [25] focused on impulsive behavior to elucidate the neurobiology of ADHD. They treated SHR with caffeine, a non-selective adenosine receptor antagonist, to evaluate the modulating effects of the adenosine systems in a tolerance to delay of reward task.…”
Section: Impulsive Behaviormentioning
confidence: 99%
“…An experiment carried out in SHR rats (an animal model reproducing some features of ADHD) evaluated the modulating effects of the cannabinoid system on impulsivity, using a delay reinforcement task and the administration of WIN55212-2 or AM251 (352). This study concluded that treatment with WIN55212-2 decreased whereas AM251 increased the choices of the large reward, suggesting that CB1r plays a relevant role in impulsive behavior.…”
Section: Animal Studiesmentioning
confidence: 98%